Hypoxia Effects in Intervertebral Disc-Derived Stem Cells and Discus Secretomes: An in vitro Study - Romaniyanto, - (Dove Medical Press, 2022)
Background: This study aimed to investigate the effects of hypoxia and normoxia preconditioning in rabbit intervertebral disc-derived stem cells (IVDSCs) and discus-derived conditioned medium (DD-CM)/secretomes in vitro. Transforming growth factor (TGF)-β1, platelet-derived growth factor (PDGF), fibroblast growth factor (FGF), and vascular endothelial growth factor (VEGF) have a role in the proliferation, development, differentiation, and migration of MSCs. Materials and methods: Intervertebral discs were isolated from rabbit and incubated in normoxia and hypoxia 1%, 3%, and 5% (hypoxia groups) condition. Cell counting was performed after 24 hours of manipulation, then analyzed using one-way ANOVA. TGF-β1, PDGF, FGF, and VEGF were measured using the ELISA. Results: The highest number of cells was in the hypoxia 3% preconditioning compared to the normoxia, hypoxia 1%, and hypoxia 5% groups. Hypoxia 3% also had the highest increase in PDGF protein production compared to normoxia, with hypoxia 1% and 5%. Among hypoxia groups, the highest secretions of VEGF and FGF proteins were in the hypoxia 3% group. Based on TGF-β1 protein measurement, the hypoxia 1% group was the highest increase in this protein compared to other groups. Conclusion: Oxygen level in hypoxia preconditioning has a role in the preparation of IVDSCs and secretome preparation in vitro. The highest cell numbers were found in the treatment group with 3% hypoxia, and 3% hypoxia was significantly related to support IVDSCs preparation. Preconditioning with 3% hypoxia had higher PDGF and VEGF levels than other hypoxia groups.